Preliminary Study on Post-Peak Behavior and Fracture Characteristics of Hard Rock Under True Triaxial Stress - Zeng, Feng; Gao, Meiben; Chen, Fujiang; Yang, Yongyi; Zhang, Yan (Frontiers in Earth Science, 2022)
The post-peak behavior and fracture characteristics of hard rock are correlated with the stability and bearing capacity of engineering rock mass. However, there are relatively few researches on the post-peak mechanical behavior and fracture characteristics of hard rock under true triaxial stress. Therefore, this paper carried out relevant true triaxial compression tests and acoustic emission (AE) monitoring. It is concluded that under true triaxial condition, the number of post-peak steps increases first and then decreases with the increasing σ2, which implys the rock failure evolves from shear failure to more complex tension-shear mixed failure, and finally evolves into a failure mode dominated by tensile failure. The overall level of rock fracture angle (θ) at low σ3 is higher than that at high σ3. In the range of stress level in this paper, when σ3 is high, the fracture angle of granite increases with increasing σ2, and its regularity is obvious, while when σ3 is low, the regularity of fracture angle increases with the increasing σ2 is not obvious. It is found that there are three different types of cacking process in granite. Meanwhile, the expansion rates of three different racking types are calculated by simplified treatment, which are about the order of 10-5-10-4 m/s. The research results of this paper could supply a useful reference for the understand of deep hard rock fracture behavior.